Variabilidade fluviométrica do rio Madeira em Rondônia e suas relações com a precipitação do satélite TRMM e oceanos tropicais - DIAS, Thaiane Soeiro da Silva (2019)
Using river level data of the Madeira river in the Porto Velho city during 36 years (1974-2010), it was evidenced that during the hydrological year, the months of November to March represent the wet (higher river level) season while the months of May to September correspond the dry (lower river level) season of the Madeira river. The TRMM satellite rainfall at high spatial resolution (0.25 °) allowed investigating the configuration of regional precipitation variability associated with the Madeira river in Porto Velho. Considering the wet period, whose annual peak occurs in March, it was found that the rainfall preceding two months (January) the flood peak is associated with the ITCZ and convection in most of Amazon region. For the month before (February) and during the peak of flood (March) the results showed the influence of frontal systems organizing tropical convection in western Amazon. For the dry period whose annual peak occurs in September, it was observed that from July to September (lags of -2, -1 and 0) the rainfall occurrence are related to the frontal systems positioned in Southeast and Central western Brazil which enhance the tropical convection causing rainfall in the region of Rondônia, which explain the fluviometric variability above the normal. The relationship between river variability and tropical Oceans showed that river level below normal periods are associated with negative SST anomalies, i.e., the La Niña episodes in the Pacific Ocean. For the wet season, correlations were noted only in the eastern Pacific and results more evident in northern and southern subtropical Atlantic Ocean.